The Influence of Lifestyle and Saving Habits on Students' Personal Financial Management in Bengkulu - Dwi Nova Adjie; Annisa Rahma Putri (Tractare: Jurnal Ekonomi-Manajemen, 2026)
This study aims to analyze the influence of lifestyle and saving habits on the personal financial management of university students in Bengkulu City. A consumptive lifestyle may affect students' spending patterns, while saving habits can encourage more planned and responsible financial behavior. This research employed a quantitative method with an explanatory research approach. The population consisted of active students from the Faculty of Economics and Business at Dehasen University Bengkulu, Bengkulu University, and Muhammadiyah University of Bengkulu. The sample was selected using stratified random sampling. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. Instrument testing was conducted through validity and reliability tests, while hypothesis testing was carried out using t-tests, F-tests, and the coefficient of determination. The results indicate that lifestyle and saving habits influence students' personal financial management. Simultaneously, both variables contribute to explaining variations in students' personal financial management in Bengkulu City. These findings highlight the importance of developing a more prudent lifestyle and strengthening saving habits to improve students' financial management capabilities.